Flow characteristics of open channels based on patch distribution of partially discontinuous rigid combined vegetation - Zhang, Jingzhou; Zhang, Shengtang; Wang, Chuantao; Wang, Wenjun; Ma, Lijun (Frontiers in Plant Science, 2022)
To clarify the flow characteristics of open channels under the combined distribution of vegetation in a patch, this study used the computational fluid dynamics tool FLUENT and the Reynolds stress model to design four combined and four discrete distribution modes under two different inundation states (submerged and non-submerged). The flow characteristics of longitudinally discontinuous rigid vegetation patches occupying half the width of the channel were numerically simulated. The numerical model is verified by indoor open channel flume experiments, and the obtained model data is in good agreement with the measured data. The results showed that: 1) The diameter of vegetation is an important factor affecting the wake structure. Under the submerged condition. 2)The submerged state, distribution pattern and combination form of vegetation are important factors that affect the distribution of flow velocity and change the structure of water flow. That is, the influence of vegetation distribution pattern on flow velocity and turbulence intensity under submerged condition is significantly weaker than that under non-submerged condition, and the flow velocity in non-vegetation area is significantly higher than that in vegetation area. The increase in the combined vegetation comprehensive stem thickness and the discrete degree resulted in an increase in the difference in flow velocity and turbulence intensity. 3) As the water flowed downstream, the flow velocity along the vegetated area continuously decreased, while it increased continuously along the non-vegetated area, and the difference in flow velocity between the two areas became more apparent. 4) The inundation state and combination characteristics of vegetation were important factors affecting the Reynolds stress of the channel location in the patch area.